Hematological- and Neurological-Expressed Sequence 1 Gene Products in Progenitor Cells during Newt Retinal Development - Tatsushi Goto; Fumio Tokunaga; Osamu Hisatomi (Stem Cells International)
Urodele amphibians such as Japanese common newts have a remarkable ability to regenerate their injured neural retina, even as adults. We found that hematological- and neurological-expressed sequence 1 (Hn1) gene was induced in depigmented retinal pigment epithelial (RPE) cells, and its expression was maintained at later stages of newt retinal regeneration. In this study, we investigated the distribution of the HN1 protein, the product of the Hn1 gene, in the developing retinas. Our immunohistochemical analyses suggested that the HN1 protein was highly expressed in an immature retina, and the subcellular localization changed during this retinogenesis as observed in newt retinal regeneration. We also found that the expression of Hn1 gene was not induced in mouse after retinal removal. Our results showed that Hn1 gene can be useful for detection of undifferentiated and dedifferentiated cells during both newt retinal development and regeneration.